It Matters to Whom You Compare Yourself: The Case of Unrealistic Optimism and Gender-Specific Comparisons. Issue 1 (January 2023) - Kulesza, Wojciech; Dolinski, Dariusz; Suitner, Caterina; Genschow, Oliver; Muniak, Paweł; Izydorczak, Kamil; Salvador Casara, Bruno Gabriel
Unrealistic Optimism (UO) appears when comparing participants' risk estimates for themselves with an average peer, which typically results in lower risk estimates for the self. This article reports nuanced effects when comparison varies in terms of the gender of the peer. In three studies (total N = 2, 468, representative sample), we assessed people's risk estimates for COVID-19 infections for peers with the same or other gender. If a peer's gender is not taken into account, previous studies were replicated: Compared with others, participants perceived themselves as less likely to get infected with COVID-19. Interestingly, this effect was qualified by gender: Respondents perceived women as less threatened than men because women are perceived as more cautious and compliant with medical guidelines.